Mewujudkan Lingkungan Belajar Islami : Kolaborasi Antara Orang tua, Mesjid dan Sekolah berdasarkan Pemikiran Abdullah Nasih Ulwan - Fitri Rahayu; Hakmi Wahyudi (CV Edujavare Publishing, 2023)
The aim of this research is to explore effective collaboration strategies among parents, mosques, and schools to create an Islamic learning environment that fosters strong character and morals for children in Indonesia. Using a library research approach, this study analyzes literature on Islamic education and the collaboration dynamics between these institutions, drawing insights from Abdullah Nasih Ulwan's perspectives. Data gathered from academic sources and digital libraries highlight gaps in implementation and propose strategies to enhance interaction and synergy among parents, mosques, and schools. Effective communication between parents and children is crucial in mitigating negative behaviors like unwanted sexual conduct among teenagers. Many parents encounter challenges in supporting their children's home study, necessitating increased support from schools and mosques. Optimizing mosques as centers for intensive spiritual education and improving school programs for holistic character development are essential. This research underscores the importance of integrated efforts among home, school, and mosque in nurturing intellectually capable and morally upright young generations who contribute positively to society and uphold their religious values.